Synovial sarcoma: a rare neoplasm of paranasal sinus - Abrar, Sehrish; Fatima Shaukat; Muhammad Atif Mansha; Agha Muhammad Hammad; Yumna Ahmed; Nasir Ali (Journal of the Pakistan Medical Association, 2023)
Synovial Sarcoma (SS) is a rare soft-tissue malignant tumour. Its presentation in the head and neck region is uncommon. Because of the complex anatomy of the head and neck region, surgery with clear margins is not achievable. In such cases, a multi-modality approach is required as there is no established standard of care. In this report, we share the case of a girl who presented with nasal obstruction. Imaging revealed a mass involving the left nasal cavity, paranasal sinuses without intracranial extension. It was diagnosed as synovial sarcoma. She underwent surgical excision and adjuvant radiation therapy (RT) to the tumour bed, followed by an incomplete course of chemotherapy. Later on, she developed systemic disease. Considering the rarity of this case and lack of guidelines for standard treatment, we report on this case to share our experience with management and treatment outcome. Keywords: Head and neck region, Synovial sarcoma, Radiotherapy, chemotherapy.